Piano technique. Consisting of two complete books "The Shortest Way to Pianistic Perfection" and "Rhythmic, Dynamics, Pedal and other Problems of Piano Playing" - Gieseking, Walter; Leimer, Karl (New York Dover, 1972)
Two books bound together, by one of greatest pianists of all time and his famed teacher: The Shortest Way to Pianistic Perfection, and Rhythmics, Dynamics, Pedal and Other Problems of Piano Playing.
Keywords: Piano; Method